Predicting response to treatment for colorectal cancer: a review of relevant mechanisms and potential biomarkers. (April 2015) - Sutton, Paul A; Jones, Rob P; Evans, Jonathan P; Kitteringham, Neil; Goldring, Chris; Palmer, Dan H; Vimalachandran, Dale; Malik, Hassan Z
Abstract : Neoadjuvant therapy for colorectal cancer offers potential oncological benefits but is associated with increased surgical risk. Predictive biomarkers would allow the personalization of this risk/benefit balance, with treatment stratified by likely response. Although current clinical application of predictive biomarkers is limited, a number of potential targets have been proposed. This review summarizes some of the approaches being used to develop predictive biomarkers for the personalization of colorectal cancer management.